Induction of labor after one previous cesarean: Predictors of vaginal birth - Saniyati Badri Bashirudin; Siti Zawiah Omar; Farah Gan; Mukhri Hamdan; Peng Chiong Tan (Elsevier, 2023)
Objective: To identify independent predictors for vaginal delivery after induction of labor after one cesarean (IOLAC). Study design: In this retrospective cohort study, the electronic medical record of 19064 women who delivered from January 2018-September 2022 in a university hospital in Malaysia were individually searched to identify cases of IOLAC. Preselected data points on characteristics and the outcome of mode of delivery were retrieved. Bivariate analysis was performed to identify predictor characteristics for the dichotomous outcomes of vaginal delivery vs unplanned cesarean delivery. Variables with crude p < 0.05 were incorporated into a multivariable binary logistic regression analysis to identify independent predictors of vaginal delivery after IOLAC. Results: 819 IOLAC cases were identified. There were 465/819 (56.5 %) unplanned cesareans deliveries. Of the 14 selected characteristics, eight had p < 0.05 on bivariate analysis. After adjustment, six characteristics, body mass index, height, ethnicity, parity, previous cesarean indication and Bishop score were independently predictive of vaginal birth but not maternal age or method of labor induction. Birthweight, labor induction indication, gestational age, haemoglobin level, diabetes and hypertension in pregnancy were not significant at the level of bivariate analysis. Conclusion: Obesity, short stature, no prior vaginal delivery, previous cesarean indicated by failure to progress, unfavorable Bishop score and ethnicity were independent predictors for unplanned cesarean after IOLAC. These predictors should help guide women and their care providers in their shared decision-making about IOLAC.